Absence of Mutations in marRAB or soxRS in acrB-Overexpressing Fluoroquinolone-Resistant Clinical and Veterinary Isolates of Escherichia coli - Webber, Mark A. (American Society for Microbiology, 2001)
The amount of acrB, marA, and soxS mRNA was determined in 36 fluoroquinolone-resistant E. coli from humans and animals, 27 of which displayed a multiple-resistance phenotype. acrB mRNA was elevated in 11 of 36 strains. A mutation at codon 45 (Arg→Cys) in acrR was found in 6 of these 11 strains. Ten of the 36 isolates appeared to overexpress soxS, and five appeared to overexpress marA. A number of mutations were found in the marR and soxR repressor genes, correlating with greater amounts of marA and soxS mRNA, respectively.